PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI BENTANG ALAM PESERTA DIDIK KELAS IV SDN PANGGREH 2 JABON SIDOARJO - Nur Hidayati; Farida Istianah; Rica Istiqfarin Al Isa (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Learning in the classroom is an important part of the education process. If the implementation of learning in class is meaningful, it can produce quality students. The teacher has a big role in organizing the class, the teacher's ability to design learning that starts from mature teaching preparation. One of them is by applying a learning model that is suitable for use in learning to be able to improve student learning outcomes. The learning model that will be applied is the Team Games Tournament (TGT). The purpose of this study was to improve the results of learning Indonesian on landscape materials for fourth grade students by applying the Teams Games Tournament (TGT) learning model at SDN Panggreh 2 Jabon Sidoarjo. The implementation of PTK is carried out through two cycles where each cycle consists of four stages, namely: planning, implementing actions, observing, reflecting. Data collection techniques used by using tests, documentation. The success indicator of this PTK is the learning outcomes or the number of students who get a score according to KKM (> 55) of at least 75%. The learning outcomes in the first cycle were 71.42% with an average value of 67.14. The learning outcomes in cycle II were 96.42% with an average value of 82.14. Based on the results of the study, it can be concluded that by applying the Teams Games Tournament (TGT) learning model, it can improve the learning outcomes of Indonesian language on landscape materials for fourth grade students at SDN Panggreh 2 Jabon Sidoarjo.